(untitled) (Fiep Bulletin - online, 2013)
Introduction: Physical inactivity is one of the major consequences of modernization with adverse health effects. Factors that reduce energy expenditure and decreased duration of physical education classes in schools, can play a critical role in the prevalence of overweight among children. Seeking to check the health of children, adolescentes, adults and the elderly in recent years, physical education professionals have resorted to the evaluation of Health Related to Physical Aptitude (HRPA) as an indirect way to analyse this condition. Some studies show decreased levels of physical aptitudes in childhood and adolescence. Goal: This study aimed to compare indicators of HRPA between boy and girls, students in the city of Duque de Caxias, Rio de Janeiro- Brazil. Methods: Participants were students of municipal schools in Duque de Caxias, aged between 10 and 14 years old attending classes regularly Physical Education curriculum. 10 schools were selected for the 1st and 4th district (5 schools in each district). Of the total of 840 students sampled were evaluated 90.0% (n = 756) and 338 girls and 418 boys. For evaluation of HRPA was used protocol PROESP (2009). Results: The test of cardiorespiratory aptitude (BG = 1145.7 ± 297.8 versus GG * = 1056.6 ± 292.7 *) and abdominal strength (BG = 27.5 ± 9.3 versus GG * = 21.6 ± 10.4 *) showed larger in boys compared with the results of the group of girls. The opposite was observed in the flexibility test (BG = 20.7 ± 6.5 versus GG * = 21.4 ± 6.3 *). In all tests, the differences were statistically significant. Conclusion: According to results we can say that the Cardiopulmonary Fitness is the component of the HRPA with a higher prevalence of inadequacy, followed by lack of Abdominal Strength, Flexibility and lack of nutritional risk. Classes Physical Education curriculum can be used as a tool to improve physical fitness in this population.